Isolation and Characterisation of the Bundooravirus Genus and Phylogenetic Investigation of the Salasmaviridae Bacteriophages - Cassandra R. Stanton; Daniel T. F. Rice; Michael Beer; Steven Batinovic; Steve Petrovski (Viruses, 2021)
Bacillus is a highly diverse genus containing over 200 species that can be problematic in both industrial and medical settings. This is mainly attributed to Bacillus sp. being intrinsically resistant to an array of antimicrobial compounds, hence alternative treatment options are needed. In this study, two bacteriophages, PumA1 and PumA2 were isolated and characterized. Genome nucleotide analysis identified the two phages as novel at the DNA sequence level but contained proteins similar to phi29 and other related phages. Whole genome phylogenetic investigation of 34 phi29-like phages resulted in the formation of seven clusters that aligned with recent ICTV classifications. PumA1 and PumA2 share high genetic mosaicism and form a genus with another phage named WhyPhy, more recently isolated from the United States of America. The three phages within this cluster are the only candidates to infect B. pumilus. Sequence analysis of B. pumilus phage resistant mutants revealed that PumA1 and PumA2 require polymerized and peptidoglycan bound wall teichoic acid (WTA) for their infection. Bacteriophage classification is continuously evolving with the increasing phages’ sequences in public databases. Understanding phage evolution by utilizing a combination of phylogenetic approaches provides invaluable information as phages become legitimate alternatives in both human health and industrial processes.